2019
DOI: 10.1002/er.4689
|View full text |Cite
|
Sign up to set email alerts
|

Design of a solar‐driven cogeneration system using flat plate collectors and evacuated tube collectors

Abstract: Summary The objective of this work is the investigation of a novel solar‐driven cogeneration system, which combines both flat plate collectors (FPCs) and evacuated tube collectors (ETCs). This system includes an organic Rankine cycle in order to produce electricity and heat exchangers in order to produce useful heating at 50°C, which is a usual temperature level for domestic applications. The combination of FPCs and ETCs aims to reduce the investment cost and so to design a cost‐effective solar‐driven cogenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…It is obvious that higher mass flow rates lead to higher thermal efficiency; however, after a certain value of mass flow rate for liquid HTFs, efficiency curves become horizontal and does not change. This fact proves that there is no reason for using higher mass flow rates by thermal/energetic point of view 40 . The same trend can be observed for sCO 2 but it happens at higher mass flow rate as compared to other two fluids.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…It is obvious that higher mass flow rates lead to higher thermal efficiency; however, after a certain value of mass flow rate for liquid HTFs, efficiency curves become horizontal and does not change. This fact proves that there is no reason for using higher mass flow rates by thermal/energetic point of view 40 . The same trend can be observed for sCO 2 but it happens at higher mass flow rate as compared to other two fluids.…”
Section: Resultssupporting
confidence: 74%
“…This fact proves that there is no reason for using higher mass flow rates by thermal/ energetic point of view. 40 The same trend can be observed for sCO 2 but it happens at higher mass flow rate as compared to other two fluids. All the investigated performance parameters increase rapidly against mass flow rate of 0.04 kg/s, but after that, less increment is observed for all the considered performance parameters.…”
Section: Exergo-environmental Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…Both the FPSC and the ETSC can provide a sufficient amount of heated water used in the organic Rankine cycle. Bellos and Tzivanidis 146 investigated a numerically novel solar‐driven cogeneration system and found that the FPSC selection size was significantly smaller than the ETSC in optimal exergetic scenarios. However, in cases of higher demand for heating output, the FPSC region is declining.…”
Section: Energy Efficiency Of Forced Circulation Etscmentioning
confidence: 99%